A Genetic Model of Impulsivity, Vulnerability to Drug Abuse and Schizophrenia-Relevant Symptoms With Translational Potential: The Roman High- vs. Low-Avoidance Rats - Giorgi, Osvaldo; Corda, Maria G.; Fernández-Teruel, Alberto (Frontiers in Behavioral Neuroscience, 2019)
The bidirectional selective breeding of Roman high- (RHA) and low-avoidance (RLA) rats for respectively rapid vs. poor acquisition of active avoidant behaviour has generated two lines/strains that differ markedly in terms of emotional reactivity, with RHA rats being less fearful than their RHA counterparts. Many other behavioural traits have been segregated along the selection procedure; thus, compared with their RLA counterparts, RHA rats display a robust sensation/novelty seeking profile, behave as proactive copers in the face of aversive conditions, and show high impulsivity and an innate preference for natural and drug rewards. Impulsivity is a multifaceted behavioural trait and is generally defined as a tendency to express actions that are poorly conceived, premature, highly risky or inappropriate to the situation, that frequently lead to unpleasant consequences. High levels of impulsivity are associated with several neuropsychiatric conditions including attention-deficit hyperactivity disorder, obsessive-compulsive disorder, schizophrenia, and drug addiction. Herein, we review the behavioural and neurochemical differences between RHA and RLA rats and survey evidence that RHA rats represent a valid genetic model to investigate the neural underpinnings of behavioural disinhibition, novelty seeking, impulsivity as well as deficits in attentional processes, cognitive impairments and other schizophrenia relevant traits, and vulnerability to drug seeking and taking.